Exploitation of a novel heterologous expression system for characterisation of fungal secondary metabolites - Geib, Elena (2018)
Aspergillus species have a great impact on economy and human health. These filamentous ascomycetes are known to cause food and feed spoilage and can act as pathogens of plants and humans. Besides these detrimental effects, several Aspergillus species have been exploited for food production and as producers of bioactive metabolites, organic acids and proteins. The study presented here focusses on Aspergillus terreus, which combines most of the features described above. A. terreus is used for production of the primary metabolite itaconic acid and the natural product lovastatin. It has been described as cause of disease on potato plants and is an emerging pathogen of humans. Investigation of the interaction of A. terreus with immune cells showed that acidification of phagolysosomes in macrophages is not inhibited by A. terreus as observed with other Aspergillus species. Since inhibition of acidification has been attributed to dihydroxynaphthalene (DHN)-melanin in Aspergillus conidia, a different type of melanin in A. terreus conidia was expected.